USABILITY SYSTEM COLLABORATIVE GROOVE NETWORKS AND TELEEDUCATION SYSTEM AS A SUPPORT FORCOURSES ON THE INTERNET - Incacari Sancho, Gerber (2007)
In this article has been determined usability of the system collaborative Groove Networks and tele-education system as a support for courses over the Internet. For this study we used the usability test that mapped the ease of use of collaborative system, this was implemented the digital platform system telelearning (Moodle), in the process of teaching that is conducted in two phases: Synchronous for Groove Networks and asynchronous for tele-education system, which were conducted over a period of four weeks, coming to the conclusion that the digital platform for tele-education system leads to the greatest number of people and be present 24 / 7 (24 hours the day and seven days a week).